PARADOKS PEMEKARAN WILAYAH (STUDI PEMEKARAN DESA DALAM KONTEKS UU DESA DI KABUPATEN LOMBOK TIMUR) - LALU MUH. KABUL (GANEC SWARA, 2022)
The previous studies on regional fragmentation showed that the condition of new region is not better than old one. This study described paradox of regional fragmentation (village) compared to the previous studies. The study method used is mixed methods, namely quantitative and qualitative. The result of study showed that based on “Status IDM” in context of Village Law it is found three village categories in East Lombok District, namely developing village, advanced village, and self reliance village. In the context of regional fragmentation, it is more new village that experienced “Status IDM” increased than old one. Meanwhile, that result of study showed the paradox, it meant that condition of new village is better than old one